Pemberian Ganti Kerugian kepada Masyarakat Terkait Pengadaan Tanah untuk Kepentingan Umum - Andriany, Vicy; Asmadia, Tezi (SAFE-Network, 2024)
The success of infrastructure projects is closely related to land acquisition/land acquisition owned by the community, it is not even possible for population relocation to occur. The implementation of development that requires land acquisition is basically a waiver of land rights. Land Procurement for Public Interest is regulated by the Government in Law No. 2 of 2012 and Other Legislations. The purpose of this study was to determine the process of land acquisition and the calculation of fair market value as the basis for providing compensation. The research method used is literature studies and displayed descriptive. Compensation is a proper and fair compensation to the rightful party in the land acquisition process. The results of the research found are based on Law No. 2 of 2012, the land acquisition process consists of 4 stages, namely planning, preparation, implementation and submission of results. Meanwhile, to provide an opinion on the value of the land, an appraisal process is carried out by a Public Appraiser as a professional independent appraiser who has a license from the Land Agency. The appraisal process for compensation includes physical (material) and non-physical (immaterial) compensation where the final value obtained by the Appraiser is Fair Market Value.